Fighting inflation in Argentina: A brief history of ten stabilization plans - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2017)
This paper seeks to identify what worked and what didn't work to stop inflation in Argentina in the last seventy years. The approach is descriptive rather than theoretical and examines the relative performance of the only ten stabilization plans that, during the period 1952-2015, lasted at least 24 months. The paper also compares the performance of these plans along other dimensions, such as economic growth, unemployment and income distribution and evaluates the impact of international economic conditions. The analysis sheds light on the debates shock vs. gradualism and orthodox vs. heterodox and puts the current stabilization plan in a historical context.
Keywords: 330; Argentina; economic policy; inflation; stabilization plans; shock; gradualism; orthodoxy; heterodoxy